Recovery from mental illness versus substance use disorder. Issue 3 (18th May 2020) - Corrigan, Patrick W.; Qin, Sang; Davidson, Larry; Schomerus, Georg; Shuman, Valery; Smelson, David
Abstract : Purpose: While serious mental illness (SMI) and substance use disorders (SUD) are common, less research has focused on causal beliefs across conditions. This is an important question when trying to understand the experience of dual diagnosis. The purpose of this paper is to examine how three factors representing causal beliefs (biogenetic, psychosocial or childhood adversity) differ by SMI and SUD. This study also examined how causal beliefs were associated with overall, process and outcome beliefs about recovery. Design/methodology/approach: Using Mechanical Turks online panel, 195 research participants from the general public completed measures of recovery – overall, outcome and process – for SMI and SUD. Participants also completed the Causal Beliefs Scale yielding three causal factors for SMI and separately for SUD: biogenetic, psychosocial and childhood adversity. Findings: Results indicated participants endorsed biogenetic cause more for SMI and SUD. Moreover, research participants endorsed biogenetic causes more than the other two for SMI. Results also showed the psychosocial cause was positively associated with recovery for SMI. Biogenetic causes were not. Almost none of the causal indicators was significantly associated with recovery for SUD. Originality/value: Implications of these findings for future research and public efforts to enhance attitudes about recovery are discussed.